Augmented release of Teretrius nigrescens Lewis (Coleoptera: Histeridae) for the control of Prostephanus truncatus (Horn) (Coleoptera: Bostrichidae) in stored cassava chips - Hell, K.; Lamboni, Y.; Houndekon, T.; Alidou, G.M. (Elsevier, 2006)
A trial was set up in northern Benin to evaluate the potential of Teretrius nigrescens to reduce the infestation and damage to cassava chips caused by storage insects. Cassava chips were stored for 5 months in mud silos and 50 adults of T. nigrescens were added when the stores were first filled. Stores where no predator was released were monitored as controls. The main storage insects observed were Prostephanus truncatus and Dinoderus spp. Initial chip weight varied between 102 and 246 g with no difference between treatments. Chip weight and number of holes on chips initially differed between treatments after 2 months of storage. After 3 months of storage, losses reached 40–50% without T. nigrescens and 30–40% when cassava chips were stored with T. nigrescens. A farmer can increase his profit by 1437 Fcfa/100 kg (1$=560 Fcfa, 1£=968 Fcfa; 1€=656 Fcfa, as on 2 December 2005) through the use of T. nigrescens because losses are reduced by 11%. Data analysis showed that there were significant differences ([Math Processing Error]) between the two treatments for the number of holes, number of insects, weight of each chip as well as damage. There were twice as many P. truncatus and holes on chips in stores where T. nigrescens was not released. The addition of the predator to farmers’ stores is an economic option for controlling losses due to insects in cassava chips.